Atlas of AI : power, politics, and the planetary costs of artificial intelligence - Crawford, Kate, 1974- (New Haven : Yale University Press, 2021)
"Kate Crawford shows how AI is a technology of extraction: from the energy and minerals needed to build and sustain its infrastructure, to the exploited workers behind "automated" services, to the data AI collects from us. She shows how this planetary network is fueling a shift toward undemocratic systems, where social institutions, knowledge, and power are being reshaped. This is an urgent, groundbreaking book about the politics of infrastructure, and how the few are benefiting at the expense of the many"--
"What happens when artificial intelligence saturates political life and depletes the planet? How is AI shaping our understanding of ourselves and our societies? Drawing on more than a decade of research, award-winning scholar Kate Crawford reveals how AI is a technology of extraction: from the minerals drawn from the earth, to the labor pulled from low-wage information workers, to the data taken from every action and expression. This book reveals how this planetary network is fueling a shift toward undemocratic governance and increased inequity. Rather than taking a narrow focus on code and algorithms, Crawford offers us a material and political perspective on what it takes to make AI and how it centralizes power. This is an urgent account of what is at stake as technology companies use artificial intelligence to reshape the world."--
Introduction -- Earth -- Labor -- Data -- Classification -- Affect -- State -- Conclusion : Power -- Coda : Space
Includes bibliographical references (pages 269-313) and index.
Kate Crawford is a senior principal researcher at Microsoft Research, the inaugural visiting chair of AI and Justice at the École Normale Supérieure, and the Miegunyah distinguished visiting fellow at the University of Melbourne. She co-founded the AI Now Institute at New York University, and leads the Foundations of Machine Learning international working group. She lives in New York City.
Keywords: Kunstmatige intelligentie; Artificial intelligence; Artificial intelligence -- Sociological aspects; Artificial intelligence -- Political aspects; Artificial intelligence